INNOVATION OF KSHARAPLOTA (MEDICATED GAUZE) IN THE MANAGEMENT OF VRANA (ULCER) - V. Shekokar, Anantkumar; M. Borkar, Kanchan (International Journal of Ayurveda and Pharma Research, 2015)
Indians have paid enough attention to discover the therapeutically effects of plants and herbs as medicinal agents in many diseases. Plants contain Alkaloids and various other chemical substances which form the base for many medical preparations. Most of the drugs used are derived from the natural world through the experiments of earlier civilization. Ksharaplota (medicated gauze) is an innovative concept used for management of infected and chronic wounds and ulcers. This Ksharaplota (medicated gauze) was prepared with the help of Snuhikshira (latex of Euphorbia neriifolia Linn.), Apamargakshara (ash of Achyranthes aspera L.) and Haridra (Curcuma longa L.). Single coating of the above drugs are given to the Plota (gauze). It can be used to heal wounds and ulcers. This Ksharaplota is prepared similarly with basic concept of Ksharasutra preparation.There are number of dressing materials given by Sushruta e.g. Pichu (cloth), Kawalika, Plota (gauze) and Vikeshika or Varti (wick). Among that we selected Plota as a dressing material which can be used as for deep and broader wounds and ulcers. In the present study preparation of Ksharaplota, advantages, indications, disadvantages, sterilization, storage, standardization were observed for simple and safest parasurgical practice.